CONSUMER ONLINE BUYING DECISIONS:- IN SPECIAL REFERENCE WITH HAPPOZ.COM PVT LTD,HYDERABAD - CHATURVEDI, MOLLY; BABU, M.KISHORE (International Journal of Psychosocial Rehabilitation, 2020)
Consumer online buying is the latest process which has emerged out of the Business to customer model,this buying process has gained significance drastically as in present competitive times ,customers is taking into consideration ease of service, less time, products under one roof, variety of goods, affordable pricing, convenient payment methods ,facilities and effective sales promotional offers .This study is undertaken in special reference with Happoz.com which deals primarily with online selling of mobile brands ,primary and secondary method of data collection is adopted .This study is being done with the online customers at Hyderabad market .In the present competitive scenario, companies are facing neck to neck competition in this market, big brands like Amazon,Flipkart,Alibaba have proved that ,if the marketing mix strategies namely Product,pricing,promotional,place mix is being implemented judiciously it will result in retaining existing customers, creating new ones and increasing the profits of thee business multifold and attainment of organizational objectives.